2011
DOI: 10.1016/j.phytochem.2011.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenosides from American ginseng: Chemical and pharmacological diversity

Abstract: Ginseng occupies a prominent position in the list of best-selling natural products in the world. Compared to the long history of use and widespread research on Asian ginseng, the study of American ginseng is relatively limited. In the past decade, some promising advances have been achieved in understanding the chemistry, pharmacology and structure-function relationship of American ginseng. To date, there is no systematic review of American ginseng. In this review, we present the different structures of the gin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
222
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 346 publications
(231 citation statements)
references
References 148 publications
6
222
1
2
Order By: Relevance
“…In the past few decades, information on certain phytochemical features as well as chemical composition of gensenosides of American ginseng has been obtained (Qi et al, 2011). Also, pharmacological effects of American ginseng have been discovered.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, information on certain phytochemical features as well as chemical composition of gensenosides of American ginseng has been obtained (Qi et al, 2011). Also, pharmacological effects of American ginseng have been discovered.…”
Section: Introductionmentioning
confidence: 99%
“…Ginseng, which has been used for thousands of years in treating a variety of diseases, has many bioactive constituents including ginsenosides, phytosterols, peptides, fatty acids, polysaccharides, polyacetylenes, vitamins, and minerals (Attele et al, 1999;Qi et al, 2011). The most active constituent of ginseng is a saponin glycoside known as ginsenosides.…”
Section: Discussionmentioning
confidence: 99%
“…Over 60 kinds of ginsenosides have been isolated from ginseng so far (Qi et al, 2011). Among which, ginsenoside Rb 1 , Rb 2 , Rc, Rd, Re, Rg 1 are the majority chemicals in ginseng that can be produced by hydrolyzing the sugar moieties whereas ginsenoside F 2 , Rg 3 , Rh 2 , compound K(CK) are rare ginsenosides and are present at low concentrations or absent in ginseng (Noh et al, 2009) (the structures of key ginseng saponins are shown in Figure 2).…”
Section: Ginsenosidesmentioning
confidence: 99%